Effect of a mirror-like illusion on activation in the precuneus assessed with functional near-infrared spectroscopy - Mehnert, Jan (Society of Photo-Optical Instrumentation Engineers, 2013)
Mirror therapy is a therapy to treat patients with pain syndromes or hemiparesis after stroke. However, the underlying neurophysiologic mechanisms are not clearly understood. In order to determine the effect of a mirror-like illusion (MIR) on brain activity using functional near-infrared spectroscopy, 20 healthy right-handed subjects were examined. A MIR was induced by a digital horizontal inversion of the subjects’ filmed hand. Optodes were placed on the primary motor cortex (M1) and the occipito-parietal cortex (precuneus, PC). Regions of interest (ROI) were defined a priori based on previous results of similar studies and confirmed by the analysis of effect sizes. Analysis of variance of the ROI signal revealed a dissociated pattern: at the PC, the MIR caused a significant inversion of a hemispheric lateralization opposite to the perceived hand, independent of the moving hand. In contrast, activity in M1 showed lateralization opposite to the moving hand, but revealed no mirror effect. These findings extend our understanding on interhemispheric rivalry and indicate that a MIR is integrated into visuomotor coordination similar to normal view, irrespective of the hand that is actually performing the task.